How does Audience Feedback affect improving problem solving skills? A study in PBL with a blended learning environment - Hikmasari, Prihatina; Asih, Tri Sri Noor; Prabowo, Ardhi (Kreano, Jurnal Matematika Kreatif-Inovatif, 2020)
This research aims to analyze the quality of audience feedback learning in the Problem Based Learning model with a blended learning environment against problem solving capabilities. The research design uses a one-shot case study of 2 classes namely experiment and control classes at SMA Negeri 8 Semarang. Data collection techniques in research using test methods, polls, observations, interviews, and documentation. The results showed that audience feedback in the Problem Based Learning model with a blended learning environment towards quality mathematical problem solving capabilities. This is demonstrated by the average validity of instruments and the performance of quality learning in good categories. The suitability of providing feedback on learning results makes students more independent in learning so as to solve problem solving of mathematics problems. Penelitian ini bertujuan untuk menganalisis kualitas pembelajaran audience feedback dalam model Problem Based Learning dengan lingkungan blended learning terhadap kemampuan pemecahan masalah matematika. Desain penelitian menggunakan one-shot case study terhadap 2 kelas yaitu kelas eksperimen dan kontrol di SMA Negeri 8 Semarang. Teknik pengumpulan data dalam penelitian menggunakan metode tes, angket, observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa audience feedback dalam model Problem Based Learning dengan lingkungan blended learning terhadap kemampuan pemecahan masalah matematika berkualitas. Hal ini ditunjukkan dengan rata-rata validitas instrumen dan keterlaksanaan pembelajaran berkualitas dalam kategori baik. Kesesuaian pemberian feedback hasil belajar menjadikan peserta didik lebih mandiri dalam belajar sehingga mampu menyelesaikan soal pemecahan masalah matematika.